Social and Demographic Characteristics of Elderly and their Lifestyle in Developing Countries: On the Example of Uzbekistan - Sherzodbek A. Inakov1, Bakhramjon B. Mamatkulov2, Khilola Kosimova3, Shoira Saidalikhujaeva4, Khadic (Institute of Medico-legal Publications Pvt Ltd, 2020)
Background: Elderly people have a variety of medical problems and functional limitations. Most older peopleexperience multiple chronic illnesses as they age, which is one of the reasons for reducing of their physicalactivity. Undoubtedly, one of the ways to prevent the occurrence and exacerbation of chronicdiseasesis tomaintain a healthy lifestyle, which increases the period of active life and helps support physical activity.Method: We used a random selection method to obtain reliable and representative data: cluster and stratifiedselection. In Tashkent city, we selected 2 clusters out of 11 clusters, where the proportion of elderly andsenile people was the highest and 674 elderly were included into the research; in the Tashkent region 3clusters were selected, and 473 elderly were included to our sample. Our sample was divided into 3 socialcategories: the first category included lonely elderly people living alone in their apartments in the amountof 310 people, the second one included lonely elderly people living in nursing homes for the elderly, in theamount of 240, and the 3rd category included elderly people living with their families, in the amount of597 people. In order to assess the respondents’ lifestyle, we studied their daily routine, dietary regimen andnature, leisure, bad habits and physical activity.Results: Married respondents were 2.1 times more among elderly living with their families, and 5.7 timesmore amongelderly living alone in their apartments compared to elderly living in nursing homes. Lonelyelderly of “middle-old” age are in more difficult state due to significant proportion of this age-category sufferwith various disabilities. It is find out that most respondents of the research do not pay proper attention toa balanced diet. Every second elderly person in our study suffered with obesity and had an increased bodymass index (BMI: 25.1<). More than half of the respondents (54.6 + 3.2%) from nursing homes smokedtobacco products 3 times more than those living with their families. Alcohol consumption among olderpeople living in nursing homes was 6 times higher compared to older people living with their families. Withan increase of the age, the number of elderly engaged in any kind of physical exercise decreased sharply.Conclusions: The study and analysis of the socio-demographic characteristics and lifestyle of elderly inUzbekistan revealed that divorce and loss of spouse are negative factors, whereas the presence of a familyand the residence of elderlywith relatives have a positive impact on their lifestyle and, accordingly, on theirhealth status.